Prevalence of Stress, Anxiety, Depression and Quality of Life in moderate to severe COVID 19 patients in West Bengal: An observational study. (Indian Journal of Public Health Research & Development, 2025)
Background: In addition to the physical symptoms COVID19 can have serious effects on people’s mental health like Stress, Anxiety, Depression, Insomnia, irritability that ultimately leads to poor quality of life [1].Though several studies have been reported the psychological consequences of COVID-19 but still there is lack of general statistics on this topic globally as it is a new strain COVID and a new pandemic situation.Method: COVID 19 infected patients who were admitted in the COVID ward were randomly selected. I obtained patients from admitted patient list which was available in control room. I Searched BHT of above patient and l checked Early Warning Sign Score (EWS score) at ward. Those EWS score having ≥ 5 and who had no previous psychiatric illness were selected as study sample.Sample Sizes were tentatively 100.  Study was conducted at post COVID follow up clinic of Department of Medicine of College of Medicine and Sagore Dutta Hospital .Written consent was taken for the study at 2 weeks follow up after discharge and at 6 weeks of follow up Perceived Stress Scale (PSS) for stress was applied . Data analyzed by appropriate statistical method.Results: 78% patients were suffering from moderate (N=78) and 22% from severe (N=22) COVID 19 infection. 57.0 % patients (N=57) were women and 43.0% (N=43) were men. The mean age of the patients was more in severe (50.6±12.8) compared to moderate (42.6±12.5) COVID-19 infection. Mean Stress was more in severe (20.18±3.36) compared moderate infection (19.0±3.2) (p=0.1397).Conclusion: Out of 100 COVID-19 patients majority were women and suffered from moderate COVID infection. Higher the age more the infection was found. Stress were more associated with the severe infection, low educated, lower socioeconomic status.Keywords: COVID-19, Stress, Anxiety, Respiratory Distress
Keywords: COVID-19, Stress, Anxiety, Respiratory Distress